Natural User Input Management (NUIM) Through Computer Architecture and Operating System in Virtual Reality - Akram, M. Salman; Naseem, Shahid; Niazi, Mushtaq; Waqas, Muhammad; Mustaasam, Tehami; Iqbal, Ayesha (Asian Journal of Social Sciences and Management Studies, 2016)
Virtual Reality (VR) takes natural user inputs (NUI), like gestures, motions, voices and produces visual overlays in digital form on top of reality that seen by different user at a time. Today’s Operating Systems don’t provide special support for VR application. As a result, today VR application are built as single hardware, single experiences, where the application itself performs as sensing and user input interpretation with machine hardware. In VR application environment new every inputs and outputs, an operating system that support VR applications needs to re-think every output and display abstraction exposed to exist applications. Disparate mouse, keyboard and other devices, which from explicit, which frequently has sensitive data mixed with user input. So, operating system with machine architecture must learn in VR applications to manage with the inherent noisiness of machine learning for recognizing for access to recognized objects like user face and skeleton in VR applications.